2018
DOI: 10.1111/jora.12407
|View full text |Cite
|
Sign up to set email alerts
|

Personal Network Characteristics as Predictors of Change in Obesity Risk Behaviors in Early Adolescence

Abstract: The potential for peers to influence obesity risk behavior increases in adolescence, yet there are knowledge gaps of how behaviors are modified in response to peers over time. This study examined how personal friendship network characteristics were associated with obesity-related behaviors from late childhood to early adolescence. Two waves of friendship, physical activity, screen time, and dietary recall data were collected from 11- to 13-year-old students (99% retention) in Australia (n = 308) over a five- t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…An Australian study examined how friendship network characteristics can be associated with obesity-related behaviors in students aged 11–13. The regression model showed that friendship networks varied by gender and behavior type, including the number of friends positively associated with physical activity intensity (in males) and screen time (in females) [ 12 ]. Thus, increased physical activity in different contexts may come from the selection of active male friends, and for girls, having more friends is associated with increased screen time [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…An Australian study examined how friendship network characteristics can be associated with obesity-related behaviors in students aged 11–13. The regression model showed that friendship networks varied by gender and behavior type, including the number of friends positively associated with physical activity intensity (in males) and screen time (in females) [ 12 ]. Thus, increased physical activity in different contexts may come from the selection of active male friends, and for girls, having more friends is associated with increased screen time [ 12 ].…”
Section: Introductionmentioning
confidence: 99%